Пантелеймон Куліш – "перший справді національний писатель український" - Івашків, В.М. (Слово і Час, 2019)
Стаття розвиває тезу І. Франка про П. Куліша як першого українського національного
письменника. У ранній період Куліш відомий переважно як фольклорист – записував і
досліджував народнопоетичну творчість у контексті її природного побутування. Письменницька
праця П. Куліша – рух від намагання цілісно відтворити багатовікову героїчну історію народу в
епопеї “Україна” до першого українського історичного роману “Чорна рада. Хроніка 1663 року”
та використання “кулішівки” – основи сучасної орфографічної системи.
Діяльність П. Куліша була підпорядкована прагненню підняти українську мову до рівня
літературної. Важливим складником його праці як національного письменника стали переклади
Біблії, творів світових класиків. The essay develops I. Franko’s statement about P. Kulish as the first truly national Ukrainian writer
who aimed at working totally for the sake of his people’s needs. The author underlines that such a
desire was Kulish’s natural urge, as the mentioned goal arose for him back in the first half of the
1840s. In particular, he planned to publish everything that vividly reflected the life of the Ukrainians
throughout centuries.
In the early period of his activity Kulish worked mainly as a folklorist. He recorded and studied
Ukrainian folklore in its natural environment. This work resulted in a unique ethnological edition “The
Notes on Southern Rus” as well as his widely known ‘farmstead philosophy’. Kulish’s writing activity
evolved from his desire to provide a complex picture of his people’s centuries-long heroic history in
the poetic epopee “Ukraine” to creating his first Ukrainian historical novel “The Commoners’ Council.
A Chronicle of 1863”. The pan-Ukrainian level of “The Notes on Southern Rus” and “The Commoners’
Council” was supported with Kulish’s own phonetic spelling system, i.e. ‘kulishivka’ which laid the
foundation of the modern orthography.
Kulish’s writing and ethnological activity was also based on his urge to raise the contemporary
Ukrainian language to the literary level. With such a purpose he published the almanac “Khata” (“The
House”) and did a lot for the full-scale functioning of the first Ukrainian literary magazine “Osnova”
(“The Foundation”). Kulish’s translation activity became another important part of his work as the first
national writer. His translations of the Bible, works by W. Shakespeare, G. G. Byron, J. W. Goethe,
F. Schiller and other outstanding classics of the world culture were significant for all Ukraine.